Explaining anomalies detected by autoencoders using Shapley Additive Explanations - Antwarg, Liat; Miller, Ronnie Mindlin; Shapira, Bracha; Rokach, Lior (Expert systems with applications, 2021)
Deep learning algorithms for anomaly detection, such as autoencoders, point out the outliers, saving experts the time-consuming task of examining normal cases in order to find anomalies. Most outlier detection algorithms output a score for each instance in the database. The top-k most intense outliers are returned to the user for further inspection; however, the manual validation of results becomes challenging without justification or additional clues. An explanation of why an instance is anomalous enables the experts to focus their investigation on the most important anomalies and may increase their trust in the algorithm. Recently, a game theory-based framework known as SHapley Additive exPlanations (SHAP) was shown to be effective in explaining various supervised learning models. In this paper, we propose a method that uses Kernel SHAP to explain anomalies detected by an autoencoder, which is an unsupervised model. The proposed explanation method aims to provide a comprehensive explanation to the experts by focusing on the connection between the features with high reconstruction error and the features that are most important in terms of their affect on the reconstruction error. We propose a black-box explanation method, because it has the advantage of being able to explain any autoencoder without being aware of the exact architecture of the autoencoder model. The proposed explanation method extracts and visually depicts both features that contribute the most to the anomaly and those that offset it. An expert evaluation using real-world data demonstrates the usefulness of the proposed method in helping domain experts better understand the anomalies. Our evaluation of the explanation method, in which a “perfect” autoencoder is used as the ground truth, shows that the proposed method explains anomalies correctly, using the exact features, and evaluation on real-data demonstrates that (1) our explanation model, which uses SHAP, is more robust than the Local Interpretable Model-agnostic Explanations (LIME) method, and (2) the explanations our method provides are more effective at reducing the anomaly score than other methods. •Explaining anomalies identified by autoencoder using shapley values.•Explain features with high reconstruction error.•Evaluated correctness and robustness of explanations.•Explanations can assist in reducing anomaly score.•Conducted experts evaluation to examine the explanation method.